2022
DOI: 10.1371/journal.pcbi.1009437
|View full text |Cite
|
Sign up to set email alerts
|

The impact of individual perceptual and cognitive factors on collective states in a data-driven fish school model

Abstract: In moving animal groups, social interactions play a key role in the ability of individuals to achieve coordinated motion. However, a large number of environmental and cognitive factors are able to modulate the expression of these interactions and the characteristics of the collective movements that result from these interactions. Here, we use a data-driven fish school model to quantitatively investigate the impact of perceptual and cognitive factors on coordination and collective swimming patterns. The model d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…The model can be elaborated and developed to include more detailed aspects of the interactions between the fish [3, 4, 8, 13, 30, 31], while the explicit directional decision-making model may be incorporated into existing models of collective animal motion [32, 33]. It remains for future exploration how this individual decision-making process can give rise to the emergence of polarized fish schools and (possibly transient) leaders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The model can be elaborated and developed to include more detailed aspects of the interactions between the fish [3, 4, 8, 13, 30, 31], while the explicit directional decision-making model may be incorporated into existing models of collective animal motion [32, 33]. It remains for future exploration how this individual decision-making process can give rise to the emergence of polarized fish schools and (possibly transient) leaders.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the model can describe the formation of cohesive shoal ("swarm") behavior, without any spontaneous alignment of the fish along a particular direction [26] (see Supplementary Movie M10). This suggests that for the maintenance of collective persistent motion along a particular direction ("schooling phase" [7,13]), the spontaneous emergence of leaders is needed [27][28][29], such as leadership by indifference (whereby less socially-responsive individuals spontaneously become leaders [27]), which is not included in the current model. Note that our model ignores the finite size of the RF, which means that we do not describe the short-range maneuvers that are necessary for collision avoidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copying of a neighbour's behaviour can create waves of altered behaviour moving across the group, which can not only transfer information, but deter predators from attacking the group [ 51 ]. Experimental work has suggested that explicit consideration of sensory cues greatly improves the ability to predict information flow in fish shoals in contrast with classic models of collective motion [ 52 ], which are now being explored in more biologically realistic models of collective movement [ 53 , 54 ].…”
Section: Rapid Timescales (Typically Less Than 1 Second and Seconds)mentioning
confidence: 99%
“…However, during this calculation, the individuals in such model frameworks do not explicitly perform a decision-making process. In other words, the direction of motion of each agent is given by some unique and continuous function of the positions and velocities of the detected (usually neighboring) conspecifics [3,4,[9][10][11][12][13]. Given two identical conspecifics, the agent in these modelas has no mechanism to spontaneously decide to follow only one of them (at a given time), in contradiction to the observations [14].…”
Section: Introductionmentioning
confidence: 99%